Development of a novel real-time polymerase chain reaction assay for the sensitive detection of Schistosoma japonicum in human stool - Sara Halili (Public Library of Science (PLoS), 2021)
Background Elimination and control of Schistosoma japonicum, the most virulent of the schistosomiasis-causing blood flukes, requires the development of sensitive and specific diagnostic tools capable of providing an accurate measurement of the infection prevalence in endemic areas. Typically, detection of S. japonicum has occurred using the Kato-Katz technique, but this methodology, which requires skilled microscopists, has been shown to radically underestimate levels of infection. With the ever-improving capabilities of next-generation sequencing and bioinformatic analysis tools, identification of satellite sequences and other highly repetitive genomic elements for use as real-time PCR diagnostic targets is becoming increasingly common. Assays developed using these targets have the ability to improve the sensitivity and specificity of results for epidemiological studies that can in turn be used to inform mass drug administration and programmatic decision making. Methodology/Principal findings Utilizing Tandem Repeat Analyzer (TAREAN) and RepeatExplorer2, a cluster-based analysis of the S. japonicum genome was performed and a tandemly arranged genomic repeat, which we named SjTR1 (SchistosomajaponicumTandem Repeat 1), was selected as the target for a real-time PCR diagnostic assay. Based on these analyses, a primer/probe set was designed and the assay was optimized. The resulting real-time PCR test was shown to reliably detect as little as 200 ag of S. japonicum genomic DNA and as little as 1 egg per gram of human stool. Based on these results, the index assay reported in this manuscript is more sensitive than previously published real-time PCR assays for the detection of S. japonicum. Conclusions/Significance The extremely sensitive and specific diagnostic assay described in this manuscript will facilitate the accurate detection of S. japonicum, particularly in regions with low levels of endemicity. This assay will be useful in providing data to inform programmatic decision makers, aiding disease control and elimination efforts. Author summary Schistosomiasis is a Neglected Tropical Disease (NTD) estimated to infect more than 230 million people worldwide. Of the various species of schistosomes that cause disease in humans, Schistosoma japonicum is considered the most virulent. As such, this pathogen presents a crucial public health threat. Typically, diagnosis of S. japonicum has been performed via the Kato-Katz technique which has been shown to dramatically underestimate the burden of infection, resulting in a need for improved detection strategies. To address this need, we have employed bioinformatic tools in order to identify a tandemly arranged, highly repetitive, DNA sequence, SjTR1, in the S. japonicum genome. Utilizing this sequence as a real-time PCR assay target, we have developed a sensitive and specific assay for the detection of S. japonicum DNA. Employment of this assay in field settings will facilitate the accurate detection of S. japonicum and provide guidance capable of informing mass drug administration efforts targeting elimination.